Medically Managed Gout Precipitating Acute Carpal Tunnel Syndrome. (September 2015) - Carr, Logan; Brooke, Sebastian; Ingraham, John
Background: The most common compressive neuropathy affects the median nerve in the carpal tunnel; it is typically chronic and progressive. Acute carpal tunnel syndrome (ACTS), on the other hand, is a less frequently encountered surgical emergency that usually occurs in the setting of trauma, such as a displaced fracture of the distal radius or carpal dislocation. To our knowledge, there are only two cases of acute carpal tunnel secondary to gout reported in the literature, with both being outside of the USA and the last case being over 20 years ago. We reviewed the literature describing acute carpal tunnel syndrome (ACTS) caused by gout and present a recent case of atraumatic ACTS caused, in part, by a tophaceous gouty mass. Methods: Review of the literature consisted of a PubMed search of all articles in the English language using the following keywords: "Acute Carpal Tunnel Syndrome" and "Tophaceous Gout" and "Gout." Results: We present the youngest reported case of atraumatic ACTS caused by tophaceous gout and the only reported case with a documented history of gout being actively medically managed with a uric acid lowering agent. This was successfully treated with an emergent extended carpal tunnel release, a complete flexor synovectomy, and excision of a gouty mass adhered to the carpal tunnel floor. Conclusions: Atraumatic ACTS secondary to gout is rare and has never been reported in a patient already being managed with uric acid lowering agents. Such a presentation requires rapid surgical exploration with release of the carpal tunnel, debridement of all gouty tissue, and increasingly aggressive adjuvant medical therapy.